Analisis Kesehatan Dan Keselamatan Kerja di PT Kimia Farma Sumatra Utara - Zahra Ananda; Susilawati Susilawati (Lembaga Pengembangan Kinerja Dosen, 2024)
PT Kimia Farmasi North Sumatra faces significant occupational health and safety problems, including high levels of worker absenteeism due to illness and significant levels of work accidents. Factors that influence this condition include exposure to dangerous chemicals, high workloads, and a lack of awareness and understanding of the importance of maintaining health in the workplace. To overcome this problem, companies can increase employee awareness through education and training programs, strengthen policies related to occupational health and safety, and improve the work environment. Companies must also improve human resource management policies related to occupational health and safety. In this way, companies can improve the quality of the work environment and company policies related to employee health and safety, as well as increase employee awareness about the importance of occupational health and safety.